ألفاظ الإثارة والبعثرة في القرآن الكريم بحث في الفروق الدلالية - الشمري خيرالله, فالح وادي (جامعة الوادي - university of Eloued, 2022)
ملخص يهدف البحث لدراسة ألفاظ تنتمي إلى حقل دلالي خاص، تدل على الإثارة والبعثرة ضمن القرآن الكريم وهي: (البعْث، والبعثرة، والإثارة، والتذرية، والنثر). والمقصود بها: التأثير في كيان مستقر، وإزالة استقراره وتغيير في حالته. والإشكالية التي يعالجها البحث يمكن صياغتها بأربعة أسئلة يعمل البحث على الإجابة عنها: هل هذه الألفاظ على مستوى دلالي واحد، فتكون مترادفة؟ أم أن لكل لفظ دلالة خاصة تجعله مستقلًا بزاوية من زوايا المعنى فتكون من الفروق؟ وهل هذه الدلالة الخاصة كانت مقصودة في القرآن؟ وهل كان يمكن إهمال هذه الفروق بحيث يمكن استعمال لفظ مكان الآخر؟ فالبحث هو دراسة دلالية لبيان الفروق بين تلك الألفاظ، واتبعْنا منهجَيْن دلاليين: منهج الحقول الدلالية، ومنهج التأثيل الدلالي، فالتأصيل يجعل الفروق الدلالية منضبطة. Abstract The research aims to study words belonging to a special semantic field, Within the language of the Holy Quran, It denotes the scattering of things, their dispersal and agitation. Which: (albeth, albaetharah, al'iitharah, altadhriah, alnathr) What is meant by it: influence on a stable entity remove its stability and change its condition. The problem that the research addresses is a complex one that can be formulated with four questions that the research works on providing an answer to: Were these words on the same semantic level, so they are synonymous? Or does each word have its own meaning? Is it a difference, not a tandem? Was this special meaning intended? Was it possible to neglect these differences so that the word "place of the other" could be used? The research is a semantic study to clarify the differences between these words. We followed two semantic approaches: The Semantic Fields theory, and Etymology, the semantic rooting makes the semantic differences rooted and disciplined. key words: the meaning, semantic differences, Synonymy, Semantic fields, Words of scatterinl.
The words of dispersal, agitation. in the holy Qur'an. a search for semantic difference
مقال
Keywords: دلالة، فروق، ترادف، ألفاظ، الإثارة والبعثرة، القرآن الكريم